SISTEM KONTROL SUHU AIR MENGGUNAKAN PENGENDALI PID. DAN VOLUME AIR PADA TANGKI PEMANAS AIR BERBASIS ARDUINO UNO - Megido, Adiel; Ariyanto, Eko (Gema Teknologi, 2016)
Adiel Megido, Eko Ariyanto  in this paper explain that the temperature control system on water heaters that use electric heaters, generally uses ON-OFF voltage control. Apart from this system being less efficient in using electricity, the limited range of voltage settings provided also lacks the output accuracy value required by the control system. So that for some applications it can cause a response to the temperature control system that oscillates. Another alternative in controlling the heating voltage is by using the PID control method (Proportional - Integral - Derifative), this method provides a wider range of voltage settings, so that it can provide the output accuracy value needed by the control system, thus making it possible to obtain system responses finer (minimum oscillation amplitude). In addition to problems with the temperature control system, the water volume control system in the water heater tank generally still uses probes that are installed at certain levels. The limitations in reading each change in height / volume of water causes the system output to be less linear (discrete). To produce linear readings and outputs in each change in water volume, a voltage divider can be used. In this final project design will use an electric water heater tank as a medium to determine the ability of the PID controller to control water temperature according to the set-point and control the height / volume of water in the tank using a voltage divider. Keywords : PID (Proporsional – Integral – Derifatif), Berosilasi, Set-pointReferencesMalvino, Albert Paul. 1981. Prinsip-prinsip Elektronik edisi kedua. Jakarta: Erlangga.Gunterus, Frans. 1994. Falsafah Dasar : Sistem Pengendalian Proses.Jakarta:Elex Media KomputindoEfendy, Marwan.n.d. Bab 1 Sistem Pengendalian. Surakarta: Universitas Muhamadiyah SurakartaBolton, W. 2009. Sistem Instrumentasi dan Sistem Kontrol. Jakarta:ErlanggaOgata, Katsuhiko. 1996. Teknik Kontrol Automatik Jilid 1-2, Diterjemahkan oleh Ir. Edi Laksono. Jakarta : Erlangga.sPetruzella, Frank D. 1996. Elektronika Industri. Yogyakarta: Andi Yogyakarta.Rashid, H Muhammad. 1999. Elektronika Daya Jilid 1. Jakarta: Prehalindo.Michael Tooley, BA. 2003. Rangkaian Elektronik Prinsip dan Aplikasi Edisi kedua. Jakarta : Erlangga.Bishop, Owen. 2004. Dasar-Dasar Elektronika. Jakarta : Erlangga.Majid, Saifulloh Agung. 2009. Pengontrolan Temperatur Menggunakan Metode Kontrol PID Berbasis Mikrokontroler AT90S8515. Semarang: Jurusan Teknik Elektro Fakultas Teknik Universitas Diponegoro.Surono, dkk. 2009. Bahasa Indonesia Untuk Perguruan Tinggi. Semarang: Farindo Press.Laksono, Suryo Krido, Sumardi, dan Aris Triwiyatno. 2010. Pengaturan Sudut Fasa Berbasis Logika Fuzzy Untuk Sistem Pengaturan Temperatur. Semarang: Jurusan Teknik Elektro Fakultas Teknik Universitas Diponegoro.Firsyari, Akhmad Salmi, Purwanto, M Aziz Muslim. 2013. Sistem Pengendalian Suhu Pada Proses Distilasi Vakum Bioetanol Dengan Menggunakan Arduino. Semarang: Jurusan Teknik Elektro Fakultas Teknik Universitas Diponegoro.Azaria Mutia Suriatmadja. 2013. Modul Kontrol Temperatur Air Berbasis PID Menggunakan Matlab Simulink. Semarang: PSD III Teknik Elektronika Jurusan Teknik Elektro Politeknik Negeri Semarang